"Bogus Tax Scheme" Using Ostensible Charity Shut Down, Penalized. Issue 6 (13th May 2019) - Unknown
Abstract : The US District Court for the District of Montana, by decision dated March 19, held that a "business" facilitating the charitable contribution and subsequent disposition of timeshares appropriately gave rise to imposition of penalties (IRC § 6700) because the appraisals were performed by unqualified appraisers and the values of property were overstated ( Tarpey v. United States ).